2010
DOI: 10.1016/j.ultrasmedbio.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Tissue Characterization Demonstrates Differences in the Left and Right Sides of the Ventricular Septum

Abstract: The left and right ventricular function of the heart are influenced by the complex structure of the ventricular septum. The cyclic variation of ultrasonic backscatter over the cardiac cycle is known to be sensitive to both structural and functional characteristics of the myocardium. The objective of this study was to investigate differences in the measured magnitude and normalized delay of cyclic variation between the left and right sides of the ventricular septum in normal adult subjects (N=31). The measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
(81 reference statements)
2
8
0
Order By: Relevance
“…It is necessary to determine a rational means of segmental differentiation. Several investigations demonstrated that the echogenic reflection arises when insonification is perpendicular to the predominant myofiber orientation, and disappears for parallel insonification . Our study also showed that different acquisition angles had influence on the reflection.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It is necessary to determine a rational means of segmental differentiation. Several investigations demonstrated that the echogenic reflection arises when insonification is perpendicular to the predominant myofiber orientation, and disappears for parallel insonification . Our study also showed that different acquisition angles had influence on the reflection.…”
Section: Discussionsupporting
confidence: 68%
“…Several investigations demonstrated that the echogenic reflection arises when insonification is perpendicular to the predominant myofiber orientation, and disappears for parallel insonification. 20,21 Our study also showed that different acquisition angles had influence on the reflection. Second, because speckle tracking uses a pattern-matching algorithm, errors in early frames can become amplified through subsequent frames.…”
Section: Limitationssupporting
confidence: 55%
“…; Holland et al. ) in which lengthening begins first in the left ventricular side (right‐handed helix). This lengthening begins before aortic valve closure.…”
Section: Ventricular Functionmentioning
confidence: 99%
“…These observations have been made by sonomicrometry 21 and by different modalities of F I G U R E 1 Five models of strips | 1449 Editorial echocardiography. [22][23][24] Therefore, even without anatomic evidence of separate muscle bands, there are two functional groups of muscle fibers.…”
Section: Studies Of Ventricular Myocardium Indicate That Myocytes Arementioning
confidence: 99%
“…The left ventricular side of the septum (right‐handed helix) contracts about 60–90 ms and relaxes about 60–90 ms before the left‐handed helix on the right ventricular side of the septum. These observations have been made by sonomicrometry and by different modalities of echocardiography . Therefore, even without anatomic evidence of separate muscle bands, there are two functional groups of muscle fibers.…”
mentioning
confidence: 99%